A rare histologic variant of Kaposi's sarcoma - Ana S. Pereira; Carolina Figueiredo; Rebeca Calado; José C. Cardoso (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
An 80-year-old male presented with a 3-year history of progressive violaceous and edematous plaques on both hands. The remaining physical examination was unremarkable and systemic symptoms were absent. All complementary investigations were negative, including serology testing for human immunodeficiency virus. Skin biopsy revealed a dermal vascular proliferation, composed of angulated vessels dissecting collagen bundles, lined by flattened endothelial cells without atypia. Immunohistochemistry showed positive staining for human herpesvirus 8, CD31, and erythroblast transformation-specific-related gene, confirming the diagnosis of lymphangioma-like Kaposi's sarcoma (LLKS). LLKS represents a rare pathological variant of all Kaposi's sarcoma (KS) subtypes, which is noticeable for the lymphangioma-like spaces that are usually only focally found. We present a case of LLKS as a variant of classic KS to raise awareness among dermatologists for this uncommon morphologic expression of KS and its distinctive histologic pattern.